Marc Chagall. - Benezra, Neal; Bruk, Jakov; Foray, Jean-Michel; McGee, Liam E.; Meyer Graber, Meret; Pacoud-Rème, Elisabeth; Pascarella, Carl; Schulmann, Didier; Exhibition. Marc Chagall. SFMOMA (San Francisco Museum of Modern Art) San Francisco. 2003-07-26. 2003-11-04 (New York San Francisco : Harry N. Abrams Inc. Publishers New York SFMOMA (San Francisco Museum of Modern Art) San Francisco, 2003)
Lavishly illustrated with more than one hundred and fifty color reproductions, MarcChagall is the first full-scale survey of the artist's work in nearly twenty years. An introductory essay by exhibition curator Jean-Michel Foray contextualizes the Russian-born artist's work, while a heavily illustrated chronology of Chagall's life assembled by Meret Meyer Graber and Jakov Bruk details the many stages of his career. The work is organized into four sections, each with an introduction by Foray, to help make sense of the aretist's prodigious oeuvre.
Marc Chagall is one of the twentieth century's favorite artists, known and admired for his rich palette, his inventive approach, his accessible subjects, and the rich traditions behind his work. Combining fantasy, spirituality, and nostalgia with a distinctive modern painting style, Chagall's canvases are infused with a joyous, dreamlike simplicity. Even as styles chifted from Cubism to Suprematism to Surrealism, his work remained individual and idiosyncratic - sometimes harming his art world reputation, but never his popular appeal.
biog. p. 38-59
Engels
boek
Keywords: Chagall, Marc